STUDI FENOMENOLOGI: PENGALAMAN PEMBELIAN PRODUK ERIGO MELALUI SHOPEE. - Farhan Bima Saputra (2023)
Social media is currently a tool that is widely used by several companies tomarket their products or services. Erigo company is a company that is quite activeon social media. One of the easiest ways now is with the help of e-commercebecause it is easy to access, can be accessed at any time, and has a wide reach. This research is structured to find out the experience of Erigo product buyers whomake purchases through Shopee and to find out the function of using e-commerceon the relevance of using Symbolic Interactionism Theory focuses onhowmeaning is formed by humans and structures in society through conversation. Ideas related to self (self) with reversal towards society are the basis used by theTheory of Symbolic Interactionism. The data collected was thoroughly utilizedfrom interviews. Based on the 10 findings on the analysis of data obtainedfrominformants through interviews based on the theory of symbolic interactionism, it can be understood that Erigo has succeeded in fulfilling 8 purchasing experienceindicators that support Erigo's brand marketing communications obtained basedon the provisions of at least 3 out of 5 sources' answers supporting the elements ineach indicator. Meanwhile, in terms of further research, it is advisabletoconsider increasing the number of interviewees which will be carried out face-toface with the addition of supporting variables and/or theories to take a deeperlook at the experiences of buyers of Erigo products and/or other brands throughe-commerce. As well as for business practitioners to be able to consider themaximum utilization of social media and e-commerce through organizingcampaigns and/or interactive content to be able to convert their target audienceinto buyers